Peran Fasilitas dan Petugas Pelayanan dalam Meningkatkan Keputusan Berkunjung ke Labuan Bajo - Gana, Hendrikus Yowanto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2024)
This research was conducted in Labuan Bajo to analyze the influence of the variables of facilities and staff service on tourists' visiting decisions using a quantitative method. The results of the descriptive analysis indicate that respondents' assessments of the research variables are generally in the good category, as reflected by the high level of agreement regarding the condition of each variable. Two independent variables were found to have a significant impact on the decision to visit. Data analysis using SPSS produced an F-value of 34.133, which is greater than the F-table value, confirming a significant influence of facilities and staff service on the visiting decision, with a coefficient of determination of 33.3%. However, this influence is not yet optimal, necessitating strategic measures to improve the quality of facilities and services. This study provides important insights for destination managers.